Determinants Affecting Willingness Of Office Workers To Use Coffee Houses Services In Bangkok During Covid-19 Outbreak - Kitcharoen, Krisana (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The purpose of this study is to investigate the determinants influencing the willingness of office workers to use coffee houses services in Silom and Sathorn areas in Bangkok during the COVID-19 outbreak. The conceptual framework presented comprises variety seeking, desire for unique products, cosmopolitanism, personal innovativeness, product evaluation, behavioral intention impact willingness to use coffee house services. The sample (n = 490) was gathered from online questionnaires using convenience and snowball sampling techniques. The study employed the Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) for the data analysis to confirm reliability, validity, goodness-of-fit of the model, and hypotheses. The findings revealed that variety seeking and personal innovativeness significantly impacted product evaluation and behavioral intention. In contrast, the desire for unique products and cosmopolitanism had no impact on product evaluation and behavioral intention. In addition, both product evaluation and behavioral intention also had a significant impact on the willingness to use coffee house services. Therefore, for practical implications, business owners and entrepreneurs could enhance product varieties to attract more customers for better sales revenue generation.